Primary pleural epithelioid hemangioendothelioma: case report and review of the literature. Issue 10 (4th July 2021) - Lavacchi, Daniele; Voltolini, Luca; Comin, Camilla Eva; Mazzoni, Francesca; Baldi, Giacomo Giulio; Briganti, Vittorio; Luvarà, Silvia; Bongiolatti, Stefano; Antonuzzo, Lorenzo
Abstract : Epithelioid hemangioendothelioma (EHE) is an extremely rare vascular sarcoma with an unpredictable clinical behavior. Pleural EHEs have been associated with poor response to treatment and reduced survival. To date, no standard treatment for EHE is available. Here we report the case of a 53-year-old man who underwent radical surgery for a symptomatic primary pleural EHE. Clinical presentation was characterized by chronic pain in the left hemithorax with transitory flare, anemia, weight loss and progressive worsening of clinical conditions. After surgery, he resumed active life and normal daily activities and, at 8 months, 18F-FDG PET and computed tomography scan showed no radiological evidence of recurrent disease. Clinical signs of this rare disease, histological features, imaging findings and functional imaging are discussed. We also report a summary of other cases with resected pleural EHE and we briefly review the role of chemotherapeutic, immunomodulatory and antiangiogenic drugs for advanced disease.